THE MANAGEMENT OF THE HEALTH SERVICES' WASTE: A PROBLEM TO BE FACED - Rafaela Gessner; Laura Christina Macedo Piosiadlo; Rosa Maria Godoy Serpa Fonseca; Liliana Müller Larocca (Universidade Federal do Paraná, 2013)
The inadequate management of Health Service Waste is harmful to environmental and population health and brings risks of work accidents. This study aimed to identify weak points in the process of management of this waste through questioning workers who function in environments with differing technological complexity. This qualitative, descriptive research was undertaken with 29 professionals responsible for the management of the waste produced in the institution, 20 working in hospital and 9 in Family Health Centers. It was possible to perceive that the professionals are partially familiar with the management of the waste, and that as it moves away from the service, its management is less known, constituting more evidence of the process of fragmentation of work in health. Understanding the management of Health Service Waste can contribute to reducing the risk of work accidents and the environmental impact of the health services' actions.